2017
DOI: 10.14196/mjiri.31.130
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Iranian nurses: A systematic review and meta-analysis

Abstract: Background: Depression is one of the most commonly diagnosed mental disorders. Nurses and other hospital service providers are a group at high risk for developing depression. Thus, knowing the prevalence of depression among nurses can help the health care decisionmakers to plan ad hoc prevention programs to control depression in this group. This study was conducted to quantitatively assess the prevalence of depression in nurses by performing a systematic review and meta-analysis. Methods: ISI/Web of Science (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
(32 reference statements)
0
11
1
Order By: Relevance
“…It has been reported that the psychological wellbeing of nurses plays a significant role in nursing care and prevention of the spread of disease in patients during pandemics such as COVID-19 (35). Accordingly, special attention to nurses and psychological support is felt strongly for promoting the care provided to patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the psychological wellbeing of nurses plays a significant role in nursing care and prevention of the spread of disease in patients during pandemics such as COVID-19 (35). Accordingly, special attention to nurses and psychological support is felt strongly for promoting the care provided to patients (36).…”
Section: Discussionmentioning
confidence: 99%
“…We may see that both student and professional nurses, especially in Asia, have a very high prevalence of depression; this prevalence is higher than even that of older patients with diseases such as stroke, hypertension, diabetes and coronary heart disease [ 47 ], and is similar to that of empty-nest elderly individuals [ 48 ]. In addition, the prevalence of depression among Chinese nurses is higher than that of nurses in Iran [ 49 ] and Chinese Hong Kong [ 50 , 51 ], Australian midwives [ 52 ], and Hungarian [ 53 ] and Australian [ 54 ] nurses. However, to our surprise, only 13.2% of nurses in Vietnam have depression [ 55 ], as well as 24.9% of Iranian nurses working in military hospitals [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mental ill-health is a serious concern in the nursing profession [19][20][21][22]; it is one of the leading causes of sickness absence in the UK National Health Service (NHS), incurring a significant financial burden to healthcare services [11]. Rates of work-related stress, emotional exhaustion and burnout are high [23,24], and the prevalence of depression may be higher in nurses than in the general population [25]. There are many complex organisational issues that may impact on nurses' mental wellbeing and care quality (e.g., staffing shortages and workload, turnover, failure to retain staff, and shift patterns).…”
Section: Introductionmentioning
confidence: 99%